The design, development and characterization of a self-replicating DNA expression technology - de Moor, Warren Ralph Josephus (Department of Pathology, 2022)
High quality T-cell immunogenicity can be an elusive type of immunity to generate and one that is often sought after by virologists, immunologists and cancer researchers alike. When T-cell immunity is generated using current methodologies the quality and magnitude of the immunological response achieved is often weak and unable to create protective immunity. Among current methods, DNA vaccines, generate highly specific T-cell immunity towards targeted antigens, and do not suffer from issues like misdirected vector targeted immunity, like viral based vectors. DNA vaccines, however, face a variety of their own weaknesses. These include, inefficient delivery, high biological loss inside the body, and the inability to counteract or avoid immediate innate cellular defence mechanisms, which limit their ability to persist inside a host cell. For these reasons, DNA vaccines are usually combined with more conventional viral vaccines in what is known as a DNA prime and viral boost regiment strategy. Combining them works well and results in improved immunity towards targeted antigens that is superior to what is obtained when either DNA or recombinant vaccines are used alone. To address many of the core issues faced by DNA vaccines, I report here on the design, development and characterization of a self-replication DNA gene expression technology. This novel DNA expression system employs a form of DNA replication (known as rolling circle replication) to generate a self-replicating DNA amplicon that can amplify its own copy number and the relative localised levels of antigen expression inside transfected mammalian cells in tissue culture and within Balb/cJ mice. These capabilities help effectively mitigate many of the core issues faced by DNA vaccines. The technology developed was shown to significantly increase gene expression for eGFP and Luciferase reporter genes, with an overall average increase in expression of approximately two-fold by 48 h post transfection in HeLa S3 cells. More specifically, an increase of at least two-fold in the absolute maximum level of the gene of interest per cell was also observed. Such localised doubling in antigen expression, at the cellular level, is believed to enhance innate immune activation and improve the overall immune response. Experimental results indicated that gene expression levels by this technology is non static in nature and appears to increase in magnitude within affected cells over time as was hypothesised. This provided strong evidence that the replication technology appears to be functioning as was expected and was able to demonstrate the ability to elevate antigen expression over time, potentially starting from extremely low and otherwise ineffective starting concentrations. This ability has potential to effectively mitigate many of the issues associated DNA vaccines such as low and ineffective delivery. This capability was observed in tissue culture as a steady increase in reporter gene expression levels across the entire range of DNA transfection levels. Furthermore, the increases in gene expression were observed to continue to amplify over time, eliminating the presence of weakly fluorescing cells in tissue culture. By 11 days post transfection, every observable cell transfected with the replication expression system, was observed to have extremely high levels of fluorescence. With recorded fluorescence levels being as bright or brighter than the highest levels obtained under normal transfections with no replicative plasmids (~48-72 h). Unique cellular responses to the presence of the replicating gene expression technology were also observed. These included an apparent slowdown in cellular metabolic activity and growth among cells transfected with replicating vectors. This was observed as a decrease in cellular division and total cell number by ~50%, by 48 h post transfection. This was accompanied by significant increases in cell size, internal cellular granularity, and gene-of-interest expression per cell. These changes were observed among all cells regardless of their relative DNA transfection level. This was demonstrated by assessment of the change in the range, mean, median, skewness and standard deviation of the cellular distribution curves for eGFP expression, cell size and internal cellular granularity. These observations provided further evidence of the dynamically changing and active nature of this technology. This also provided evidence that the replicating gene expression technology has a definitively different kind of cellular impact and effect on transfected cells compared to non-replicating DNA expression systems. Pilot studies to test the technology in Balb/cJ mice indicated, the technology appears to be functional within this animal model and was able to increase gene of interest (eGFP) expression levels compared to an equivalent non-replicating DNA expression vector control. Furthermore, these animal experiments also demonstrated significant increases in the maximum possible level of expression achieved within localised ‘hot spots' of muscle fibre bundles. This effect appeared to increase following transient addition of additional replication associated protein (Rep), giving further evidence this technology appears to be functional within the Balb/cJ animal model. Suggesting that the rate at which the replication amplification process occurs, may also be manipulated by adjusting Rep concentration. Finally, an antiviral response gene array was run to look for evidence that the replicating gene expression technology could increases antiviral response gene activation, to possibly improve T-cell activation and immunity. The array provided evidence improved antiviral response gene activation was occurring however the data was inconclusive in nature and further investigation is needed to verify these preliminary findings. The array also showed significant evidence of Rep induced Caspase 10 (CASP10), gene suppression. This suggests that Rep may play a role in the survival and virulence ofBFDV by acting as a suppressor of cellular apoptosis in a concentration-dependant manner and is worth investigating further.